The Influence of Sales Growth, Financial Distress, Leverage, and Firm Size on Prudence: A Study on Mining Sector Companies Listed on the Indonesia Stock Exchange - Pamela, Inge Lucky; Evana, Einde (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This research examines how sales growth, financial hardship, leverage, and company size affect accounting prudence in Indonesia Stock Exchange-listed mining businesses from 2019 to 2023. Modern financial reporting encounters market volatility and management uncertainty, emphasising the need to recognise losses sooner than profits. Stakeholders depend on financial statements. The mining business is high-risk and complicated, thus financial anomalies highlight the need for open and careful accounting. This quantitative study uses multiple linear regression analysis on 213 firm-year observations. The results show that sales growth and company size do not impact prudence. Financial crisis reduces prudence, implying that struggling enterprises are less careful to retain shareholder trust. Leverage increases caution since highly leveraged enterprises report more cautiously to satisfy creditors. This research emphasises the importance of financial health and debt structure in Indonesian mining accounting prudence.